A game theoretic taxonomy of social dilemmas - Martin Beckenkamp (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2002)
Both social psychology and experimental economics empirically investigate social dilemmas. However, these two disciplines sometimes use different notions for very similar scenarios. While it is irrelevant for economists whether an experimental public-good game is conceptualised as a take-some or give-some game? i.e. whether something is conceptualised as produced or extracted ? it is not irrelevant for some psychologists: They grasp public-good games as give-some games. And, whereas most economists define social dilemmas in reference to a taxonomy of goods, some psychologists think that dominant strategies are a necessary attribute. This paper presents a taxonomy that relies on a formal game-theoretic analysis of social dilemmas, which integrates and clarifies both approaches. Because this taxonomy focuses on the underlying incentive structure, it facilitates the evaluation of experimental results from both social psychology and experimental economics.
Keywords: 330; Gefangenendilemma; Klassifikation; Spieltheorie; Theorie